Effect of Application of Natural Polyphenol Containing Polymer Coatings on Quality of Pork Balls - Rao, V. Giridhara; Mallika, E. Naga; Rao, B. Eswara (Journal of Meat Science, 2019)
An attempt was made to evaluate the quality of pork balls coated with starch (T1), starch incorporated with 1% Tannic acid (T2), and  starch incorporated with 1% Quercetin (T3) and were analyzed at regular intervals of 5 days and 15 days under refrigeration (4 ± 1OC)  and frozen storage temperatures (-18 ± 1OC) respectively. The values of pH, TBA, PV, TPC and per cent water loss of the coated pork  balls increased significantly (P
Keywords: Pork balls; Polymer coatings; Quercetin; Starch; Tannic acid